Real-world effectiveness of belimumab and anifrolumab in systemic lupus erythematosus: comparable trends in disease activity and glucocorticoid reduction - Ryota Sato; Masaru Shimizu; Yuya Kondo; Kazushi Maruo; Yuki Kuroda; Hiroshi Ebe; Mizuki Yagishita; Naoto Umeda; Seiji Mogi; Ayako Ohyama; Ayako Kitada; Saori Abe; et al. (Immunological Medicine, 2025)
Despite the proven efficacy of belimumab and anifrolumab for SLE, their relative effectiveness remains uncertain owing to conflicting indirect comparison studies. We conducted a comparative effectiveness study using multicenter health records to evaluate the adjusted 12-month changes in the SLE Disease Activity Index 2000 (SLEDAI-2K), glucocorticoid dose, anti-DNA antibody titers, and CH50 levels, along with the adjusted hazard ratios of discontinuation and adverse events. A total of 58 bionaïve lupus patients (belimumab: 36, anifrolumab: 22) who initiated belimumab or anifrolumab on or after January 1, 2022 were identified and followed for up to 2 years. Adjusted changes in the SLEDAI-2K, glucocorticoid dose, and anti-DNA antibody titers were similar, with between-group differences (belimumab – anifrolumab) of −0.4 SLEDAI-2K units (95% CI: −4.8, 4.0), 1.4 mg/day (95% CI: −5.1, 7.9), and −2.7 IU/mL (95% CI: −27, 21), respectively. Belimumab was associated with a greater increase in adjusted CH50 levels (between-group difference: 5.3 CH50/mL, 95% CI: −8.9, 20) and a lower adjusted hazard ratio of discontinuation (0.68, 95% CI: 0.12, 3.7). Infection was the most common adverse event (belimumab: 31%, anifrolumab: 41%). Our findings suggest both treatments provide similar effectiveness, with belimumab offering potential benefits in CH50 levels, treatment continuity, and infection risk.